Quality and equitable education in primary and secondary schools in Zimbabwe - Muzvidziwa, Irene (African Journals Online, 2021)
Families, communities, schools and churches play a crucial role in reducing or reinforcing both social and educational inequalities in Zimbabwe. Leadership in schools plays a pivotal role in ensuring discipline and promoting quality education in their institutions. This paper seeks to highlight the issues that affect schools in their efforts to achieve quality and equitable education in Zimbabwe. The study on which the paper is based adopts a qualitative research design. Experiences of a selected group of women school heads are used to discuss some of the challenges that constrain schools to achieve quality and equitable education. Views and experiences of participants were described through in-depth interviews which were dialogical in nature .What emerged is the importance of leadership and school community partnership in achieving quality and equitable education.